An LMNA synonymous variant associated with severe dilated cardiomyopathy: Case report. Issue 2 (15th October 2021) - Gao, Shanshan; Mumme‐Monheit, Abigail; Chen, Suet Nee; Spector, Elaine B.; Slavov, Dobromir; Baralle, Francisco E.; Bristow, Michael R.; Mestroni, Luisa; Taylor, Matthew R. G.; ,
Abstract: Dilated cardiomyopathy (DCM) is one of the most common cardiac phenotypes caused by mutations of lamin A/C ( LMNA ) gene in humans. In our study, a cohort of 57 patients who underwent heart transplant for dilated cardiomyopathy was screened for variants in LMNA . We identified a synonymous variant c.936G>A in the last nucleotide of exon 5 of LMNA in a DCM family. Clinically, the LMNA variant carriers presented with severe familial DCM, conduction disease, and high creatine‐kinase level. The LMNA c.936G>A variant is novel and has not been reported in current genetic variant databases. Sanger sequencing results showed the presence of LMNA c.936G>A variant in the genomic DNA but not in the cDNA derived from one family member's heart tissue. Real‐time quantitative polymerase chain reaction showed significantly lower LMNA mRNA levels in the patient's heart compared to the controls, suggesting that the c.936G>A LMNA variant resulted in reduced mRNA and possibly lower protein expression of LMNA . These findings expand the understanding on the association between synonymous variant of LMNA and the molecular pathogenesis in DCM patients.